Penerapan Metode Demontrasi pada Mata Pelajaran Fiqih terhadap Siswa Madrasah Diniyah - Mudhofar; Nurhalimah, Evi (JURNAL PUSAKA, 2023)
This research was conducted due to the low understanding of the students, the learning process never used the method in fiqh class III Madrasah Diniyah Ali Makiniyyah Bulupitu, Gondanglegi. Based on the results of the UH (Daily Test) in the even semester of 2022-2023, out of 22 students, only 6 students whose grades reached the KKM and 16 students are still incomplete. The model used by researchers as a reference for class action research is Kurt Lewin's model in which there are four stages of empathy, namely planning, acting, observation, reflection. The subjects of this study were students of class III Madrasah Diniyah Al Makiniyyah Bulupitu, Gondanglegi consisting of 22 students. Data collection was carried out by researchers through observation, documentation of UH scores (Daily Repeat) for fiqh subjects in even semester 2022-2023, interviews, written tests, and documentation. The results of the study are as follows: (1) The application of the demonstration method obtained from observations of teacher activity and student activity in cycle II, namely 80.8 (good) and in cycle III increased to 93 (very good). Meanwhile, the observation results of students in cycle II were 82.8 (good) and in cycle II it increased to 93 (very good). (2) The understanding of the fiqh subject on prayer fardhu material using the demonstration method has increased. This can be seen from the average value of students in fiqh subjects on fardhu prayer on pre-cycles which is 62.5 with a percentage of 27.27% (less). In cycle II it became 68.1 with a percentage of 45.45% (less). In cycle III it increased to 83.18 with a percentage of 81.81% (very good). Key words: demonstration; education; fiqh; implementation; Islam